1993
DOI: 10.1037/0278-6133.12.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders in children.

Abstract: Many children experience some type of sleep problem. Often, these are transient problems with no long-lasting sequelae. But in certain cases, sleep problems may significantly impact on functioning and well-being. Sleep disorders in children can be classified into two major categories. Dyssomnias include those disorders that result in difficulty either initiating or maintaining sleep or involve excessive sleepiness. Parasomnias are disorders that disrupt sleep after it has been initiated but do not result in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
11

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(96 citation statements)
references
References 96 publications
4
81
0
11
Order By: Relevance
“…Nevertheless, at age 13 years, sleepwalking was still persisting in 24.1% of sleepwalkers (3.3% of the total sample). Sleepwalking and night terrors were originally reported to be more frequent in boys than in girls 20,42,43 ; however, these studies were based on clinical impressions rather than on epidemiologic data. No significant gender differences were seen for either sleepwalking or night terrors in the present study, as also found in numerous previous studies.…”
Section: Sleepwalkingmentioning
confidence: 99%
“…Nevertheless, at age 13 years, sleepwalking was still persisting in 24.1% of sleepwalkers (3.3% of the total sample). Sleepwalking and night terrors were originally reported to be more frequent in boys than in girls 20,42,43 ; however, these studies were based on clinical impressions rather than on epidemiologic data. No significant gender differences were seen for either sleepwalking or night terrors in the present study, as also found in numerous previous studies.…”
Section: Sleepwalkingmentioning
confidence: 99%
“…For instance, the Diagnostic Classification Steering Committee's (1990) diagnostic system includes, in its category of dyssomnias, sleep problems that appear to be genuine diseases of childhood, such as narcolepsy, and behavioral problems such as "limit-setting sleep disorder." Finally, reviews that adhere in some degree to these classification systems (e.g., Doleys, Weiler, & Pegram, 1982;Dollinger, 1977;Mindell, 1993) France, 1989;Sanders, Bor, & Dadds, 1984). A child who has never settled into appropriate sleep patterns has primary ISD.…”
Section: Behavioral Analysismentioning
confidence: 99%
“…Kahn et al (1989) reported that 43% of school-age children experienced persistent sleep problems, with 14% specifically experiencing persistent trouble sleeping. Sleep problems are also moderately stable in childhood (Gregory & O'Connor, 2002;Mindell, 1993). Kataria, Swanson, and Trevathan (1987) reported that the large majority of children in their sample with sleep problems continued to have sleep problems at follow-up 3 years later.…”
Section: Introductionmentioning
confidence: 99%